Analisa Kerangka Konseptual Teori 14 Kebutuhan Dasar Virginia A. Henderson dalam Asuhan Keperawatan Hipertensi - Fina Tri Puspitasari; Irna Nursanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the application of Henderson's conceptual framework to nursing care for patients with hypertension. The research method used was a case study to evaluate the fulfillment of 14 basic needs in a patient with hypertension who presented with complaints of headache, dizziness, an unhealthy lifestyle, anxiety, and a lack of knowledge about their condition. The results showed that the patient's biological needs, such as a high-salt diet, smoking, lack of physical activity, and sleep disturbances, were not optimally met. Psychological aspects revealed anxiety and knowledge deficits, while sociological aspects indicated limitations in work and recreational activities. Spiritual needs were well met. The resulting nursing diagnoses included acute pain, knowledge deficit, activity intolerance, and risk of spiritual distress. Interventions were provided based on the Indonesian Nursing Intervention Standards (SIKI), encompassing observation, therapeutic interventions, education, and collaboration. The evaluation results showed an increase in the patient's knowledge, ability to manage pain, and improvement in daily activities. In conclusion, Henderson's theory is practical as a framework for holistic assessment and intervention in patients with hypertension; however, further conceptual strengthening is still needed in certain chronic clinical conditions. Keywords: Case Analysis, Nursing Care, Hypertension, Virginia Henderson, 14 Basic Needs